Handbook of modern electronics and electrical engineering - Charles, Charles (New York John Wiley & Sons, 1986)
This handbook adopts a fresh approach. It is designed to provide service to engineers in fields other than electronics, to practingcing electronics engineers, to management personnel, and to anyone else needing this kind of specialized information.
Keywords: Khoa học Máy tính